Oxynoemacheilus kottelati, a new species from the Havran and Karınca streams in Northern Aegean Basin, Türkiye (Teleostei, Nemacheilidae) - Davut Turan; Sadi̇ Aksu; Sali̇m Serkan Güçlü; Gökhan Kalaycı (Zoosystematics and Evolution, 2024)
The taxonomic status of the Oxynoemacheilus from the Karınca and Havran streams in the north Aegean Basin was evaluated, and it was concluded that these populations contain a new species. The new species, Oxynoemacheilus kottelati sp. nov., is distinguished by a body with a marbled pattern, a deeper caudal peduncle, a shorter caudal peduncle, a wider interorbital distance, and a shorter middle caudal-fin lope. Oxynoemacheilus kottelati sp. nov. is differentiated from the closest species, O. marmaraensis, in possessing 51 nucleotide substitution sites, a genetic distance of 8.40%, the presence of an axillary lobe at the base of the pelvic fin (vs. absent), and a narrower median incision in the upper lip (vs. absent). Three species delimitation tests (ASAP, ABGD, and PTP) and phylogenetic analyses reinforce the validity of O. kottelati sp. nov. as a distinct species.